CPC and MST: forms and productive dynamics of the Brazilian political theater in two historical times - Villas Boas, Rafael Litvin (Univ Sao Paulo, Escola Comunicacoes & Artes, 2019)
The article aims to reflect on the conditions of production, on the evolution of forms from the concrete experience of theatrical work articulated to the demands of political organizations, considering the experiences of the 1960s, in particular the Popular Culture Center of the National Union of Students (CPC), in comparison with the theatrical experience developed by the Landless Workers Movement (MST) and theater collectives bound to it. The argument aims to articulate the narrative of experiences with the editorial effort to disseminate the work of theoreticians, directors and emblematic organizations of the Brazilian and international political theater and aims to point out similar characteristics among the organizations, despite the differences of contexts, which signify measures of construction of a popular political culture in Brazil.
Keywords: Political theater; Political culture; Productive dynamics